Reflexiones sobre gestión y derecho ambiental en el Perú. Introducción al Dossier - Ortíz Sánchez, Iván (2025)
This article offers a brief historical and regulatory review of environmental management and environmental law in Peru, presenting some reflections on the challenges and issues of sustainable development. It also introduces the articles published in issue No. 15 of the Revista Kawsaypacha: Sociedad y Medio Ambiente (Kawsaypacha Journal: Society and Environment), which has been divided into three sections featuring highly interesting contributions and research.